2-Amino-5-fluorobenzoic acid - K. Gunasekaran; B. S. Palakshamurthy; P.A. Suchetan; K.E. ManojKumar; S. Sreenivasa (Acta Crystallographica Section E, 2013)
In the title compound, C7H6FNO2, the molecule is almost planar (r.m.s. deviation for the non-H atoms = 0.015 Å) and an intramolecular N—H...O hydrogen bond closes an S(6) ring. In the crystal, inversion dimers linked by pairs of O—H...O hydrogen bonds generate R22(8) loops. Weak N—H...F hydrogen bonds, short F...F contacts [2.763 (2) Å] and aromatic π–π stacking interactions [centroid–centroid separation = 3.5570 (11) Å] are also observed in the crystal structure.